Wildfire Risk Reduction in Arizona's Interior Chaparral - Schalau, Jeff (College of Agriculture and Life Sciences, University of Arizona (Tucson, AZ), 2010)
6 pp. === Firewise Series === This bulletin describes the specific characteristics and fire history of Arizona interior chaparral which distinguish it from California chaparral, and provides landscaping guidelines both to mitigate structural damage from wildfire and to maintain the health of this important vegetation type.